TINJAUAN YURIDIS PROSES PENGISIAN JABATAN GUBERNUR DAN WAKIL GUBERNUR DAERAH ISTIMEWA YOGYAKARTA MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2012 - Akhmad Khisni (UNISSULA, 2014)
The Republic of Indonesia recognizes and respects the local government units that are special or specific regulated by law. The state also respects units of indigenous peoples and their traditional rights as long as they live and in accordance with the development of society and the principles of the Republic of Indonesia, which is regulated by law. Given the above, the implementation of local elections in the area affected by the units of indigenous peoples and the traditional rights all still alive and in accordance with the development of society.The dynamics of the special areas that must be respected by the state in accordance with Article 18 paragraph (1) of the Constitution of the Republic of Indonesia Year 1945, while the practical implications are the results of this study can be used as a recommendation Government to review the legislation that is expected to accommodate matters relating to the electoral system that is privileged Regional Head.